Kunming mouse strain is less susceptible to elastase‐induced abdominal aortic aneurysms. Issue 1 (7th December 2021) - Liu, Haole; Tian, Kangli; Xia, Congcong; Wei, Panpan; Xu, Boyu; Fu, Weilai; Li, Yankui; Li, Yafeng; Bai, Liang; Wang, Rong; Wang, Weirong; Xu, Baohui; et al.
Abstract: Background: Porcine pancreatic elastase (PPE) is successfully used to induce abdominal aortic aneurysm (AAA) in mice. However, differences between mouse strains in susceptibility to PPE induction have been reported. Kunming mouse is one of the most frequently used strains in China but whether it is suitable for induction of AAA by PPE application remains unclear. Methods: PPE infusion (1.5 units/ml) in temporary controlled aorta was performed to induce AAAs in both C57BL/6J and Kunming mice. Phosphate‐buffered saline (PBS) application was used as vehicle control. The aorta diameters of all mice were measured at days 0 and 14 after surgery to evaluate the AAA formation. Results: After 14 days of PPE or PBS infusion, all mice were sacrificed and aorta tissues were collected for histological staining analysis. At the 14th day after infusion, PPE successfully induced aortic dilation in Kunming mice and typical AAA in C57BL/6J mice. The aorta diameter increased by 0.23 mm in Kunming mice after PPE infusion, while it was 0.72 mm in the C57BL/6J strain. PPE induced mild elastin degradation, smooth muscle cell (SMC) depletion and mural leucocyte infiltration in Kunming mice, but in PPE‐sensitive C57BL/6J mice, it induced total loss of SMCs, elastin disappearance and diffused infiltrated leucocytes in aortic aneurysmal segments. The effects of PPE in inducing angiogenesis and upregulating matrix metalloproteinase 2 and 9 expression in Kunming mice were also weaker than that in C57BL/6J mice. Conclusion: At the reported dose of PPE, Kunming mouse is not as susceptible to AAA formation as C57BL/6J mice. The failure of PPE to induce AAA formation in Kunming mice may be associated to its inability to boost a strong inflammatory response.